S-acylation-dependent association of the calcium sensor CBL2 with the vacuolar membrane is essential for proper abscisic acid responses - Batistič, Oliver (Nature Publishing Group, 2012)
Calcineurin B-like (CBL) proteins contribute to decoding calcium signals by interacting with CBL-interacting protein kinases (CIPKs). Currently, there is still very little information about the function and specific targeting mechanisms of CBL proteins that are localized at the vacuolar membrane. In this study, we focus on CBL2, an abundant vacuolar membrane-localized calcium sensor of unknown function from Arabidopsis thaliana. We show that vacuolar targeting of CBL2 is specifically brought about by S-acylation of three cysteine residues in its N-terminus and that CBL2 S-acylation and targeting occur by a Brefeldin A-insensitive pathway. Loss of CBL2 function renders plants hypersensitive to the phytohormone abscisic acid (ABA) during seed germination and only fully S-acylated and properly vacuolar-targeted CBL2 proteins can complement this mutant phenotype. These findings define an S-acylation-dependent vacuolar membrane targeting pathway for proteins and uncover a crucial role of vacuolar calcium sensors in ABA responses.